Proceedings of the AeU International Research Conference: papers presented - School of Graduate Studies, SGS (AeU, 2016)
The publication consists of selected conference papers presented at the 4th October 2015 AeU International Research Conference. It covers all types of empirical and conceptual research issues pertaining to Business Administration, Education, ICT Management, Social Sciences and Humanities. The objective was to provide a platform for researchers to discuss and share their knowledge, experience and findings, thus promoting a research culture among students and alumni of the University.The